Rethinking self-discovery through ethical choice in Han Suyin’s The Mountain is Young - Hu, Xiaoling; Ali Termizi, Arbaayah; Toh Haw Ching, Florence (International Islamic University Malaysia, 2025)
Han Suyin’s The Mountain is Young (1958) portrays the love story of a married Eurasian woman in Kathmandu. While the remarkable love story unfolds alongside the protagonist’s struggle against the rigid European colonial morality, many studies primarily focus on the woman’s self-discovery and spiritual awakening through romantic love, failing to explore the ethical implications behind her choices that lead to self-discovery. Nie Zhenzhao’s ethical literary criticism highlights that the ethical dilemmas and choices of characters influence their actions and the progression of plot within the literary works. Drawing on Nie’s framework, along with postcolonial concepts of neocolonialism and Otherness, this study examines the ethical dilemmas and choices faced by a married Eurasian woman in Nepal’s post-colonial period, focusing on how these moral struggles shape her self-discovery. Examining her ethical choices, this study argues that the Eurasian woman’s search for self is essentially an ethical issue, resulting from the moral dilemmas imposed by European colonial standards. An ethical literary analysis of the Eurasian woman’s self-discovery not only offers a new perspective on the novel but also reveals the ethical choice of a female Eurasian writer to resist the old colonial ethical order in the post-colonial period.